The relationship between childhood and adult trauma and the severity of psychiatric symptoms in adults with schizophrenia in Uganda - Samanga, Rufaro Catherine (My University, 2021)
Background: Studies conducted in high and low-income countries suggest that childhood trauma is related to the onset of schizophrenia. A growing body of research mainly from high income countries suggests a relationship between recent adverse life events (adult trauma) and psychosis. However, there is a paucity of data of the effect of adult trauma schizophrenia symptoms in low-to-middle-income countries, especially African countries. This cross sectional, secondary data analysis examined the effect of both childhood and adult traumatic events among cases with severe schizophrenia and the relationship between cumulative childhood and adult traumas on the severity of schizophrenia in a sample in Uganda. Methods: Data were retrieved from the Severe Mental Illness in HIV Endemic Uganda cohort study. Cases with schizophrenia were recruited from the Butabika National Psychiatric Referral Hospital and the Masaka Regional Referral Hospital in Uganda. Childhood trauma was measured using the Childhood Trauma Questionnaire-Short Form and adult trauma was measured using the European Parasuicide Study Interview Schedule I. Adjusted left censored regression and ordinal logistic regression models were employed to estimate individual and cumulative childhood and adult traumatic events in 314 patients with schizophrenia. Results: The overall symptom severity score was significantly associated with overall adult trauma score (p = 0.009). Physical neglect, emotional and physical abuse during childhood contributed to the severity of specific positive symptoms namely delusions, disorganized speech, and negative symptoms (restricted emotional expression or avolition). Sexual abuse during adulthood was associated with severe hallucinations (OR 18.52, 95 % CI 1.93; 178.28). Adherence to oral psychiatric medication was associated with severe disorganised speech (OR 3.51, CI 1.25–9.82) while a higher BMI was associated with severe delusions (OR 0.92, CI - 0.154–0.014). Comorbid depression was associated with severe hallucinations (OR 2.28, CI 1.05–4.92). Cumulative adult traumas increased the odds of severe schizophrenia, especially hallucinations, delusions and abnormal psychomotor behavior in a dose-response manner. Conclusion: Adult trauma is significantly associated with the prognosis of schizophrenia. Specific sub-types of childhood trauma were also implicated in prognosis with regards to both positive and negative symptoms. This knowledge is useful in designing future studies and treatment approaches to patients with severe mental illness where both early-life and recent 2 life adversities should be screened for and managed. Future work should look into the effect of adult traumatic events other than physical and sexual abuse. Furthermore, studies investigating the differential effect of childhood and adult trauma among patients with comorbid psychiatric disorders will be of tremendous value
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science (Biostatistics and Epidemiology) to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2021